2011
DOI: 10.1039/c1cc15569e
|View full text |Cite
|
Sign up to set email alerts
|

One-pot reduction of graphene oxide at subzero temperatures

Abstract: We report a new reducing agent system: hydriodic acid with trifluoroacetic acid, which can chemically convert graphene oxide into reduced graphene oxide at temperatures below 0 °C in solution. This is the first achievement to produce reduced graphene oxide at subzero temperature with a mass production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
192
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 437 publications
(228 citation statements)
references
References 34 publications
33
192
1
1
Order By: Relevance
“…1B shows the Raman spectra of GO, Pt@rGO and Pd@rGO. The presence of D peak around 1344 cm −1 in GO is due to the lattice distortion of sp 2 bonded carbon atoms after the oxidation of graphite, while G peak is the characteristic peak of sp 2 bonded carbon atoms [36,37]. After the reduction of GO, I D /I G ratio increases from 1 to 1.15 and the G peak is shifted from 1585 to 1581 cm −1 and there is also enhancement in the 2D and S3 peak around 2661 and 2918 cm −1 (ESI-1) which is also a good agreement of GO reduction.…”
Section: Resultsmentioning
confidence: 99%
“…1B shows the Raman spectra of GO, Pt@rGO and Pd@rGO. The presence of D peak around 1344 cm −1 in GO is due to the lattice distortion of sp 2 bonded carbon atoms after the oxidation of graphite, while G peak is the characteristic peak of sp 2 bonded carbon atoms [36,37]. After the reduction of GO, I D /I G ratio increases from 1 to 1.15 and the G peak is shifted from 1585 to 1581 cm −1 and there is also enhancement in the 2D and S3 peak around 2661 and 2918 cm −1 (ESI-1) which is also a good agreement of GO reduction.…”
Section: Resultsmentioning
confidence: 99%
“…This value suggests again a partial GO reduction, in agreement with the results of TG-MS and XRD measurements, for reduced graphene oxide (rGO). Cui et al 52 found an I D /I G ratio of 1.4, a value of 1.9 was observed for rGO reduced by HI at 100 °C 61 . However, it is difficult to compare the results, since the measurements are often recorded on GO with different edge thickness 60,62 .…”
Section: Samplementioning
confidence: 99%
“…The TGA scan, figure 7(b), of GO clearly shows that there is a mass loss upon heating. Some of the mass-loss in the temper ature range of 25-165 °C can be attributed to the water loss, CO and CO 2 [45], despite having dried the GO previously. The chemical transition of GO to rGO occurs at approximately T = 165 °C (see figure 7(b)), a temperature which was also observed by Cui et al [45] for this process.…”
Section: Nematic To Isotropic Phase Transitionmentioning
confidence: 99%
“…Some of the mass-loss in the temper ature range of 25-165 °C can be attributed to the water loss, CO and CO 2 [45], despite having dried the GO previously. The chemical transition of GO to rGO occurs at approximately T = 165 °C (see figure 7(b)), a temperature which was also observed by Cui et al [45] for this process. Above 165 °C, the hydrophobic nature of rGO dominates dispersion stability and results in flocculation or aggregation, and consequently rGO does not form LC phases in aqueous media [26].…”
Section: Nematic To Isotropic Phase Transitionmentioning
confidence: 99%